2021
DOI: 10.1038/s41598-021-85949-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential novel biomarkers for chronic lung allograft dysfunction and azithromycin responsive allograft dysfunction

Abstract: Chronic Lung Allograft Dysfunction (CLAD), manifesting as Bronchiolitis Obliterans Syndrome (BOS) or Restrictive Allograft Syndrome (RAS), is the main reason for adverse long-term outcome after Lung Transplantation (LTX). Until now, no specific biomarkers exist to differentiate between CLAD phenotypes. Therefore, we sought to find suitable cytokines to distinguish between BOS, RAS and Azithromycin Responsive Allograft Dysfunction (ARAD); and reveal potential similarities or differences to end-stage fibrotic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…They include multi-breath nitrogen wash-out to evaluate small airway function, different imaging modalities and analytic strategies (e.g. high-resolution computed tomography), novel assessments of immune cell counts, chemokines, cytokines, and circulating cell free DNA ( Belloli et al, 2021 ; Shtraichman and Diamond, 2020 ; Tissot et al, 2019 ; Veraar et al, 2021 ). Some groups are also investigating computational models to estimate a recipient’s risk of CLAD using clinical and multi-omic databases ( Koutsokera et al, 2017 ; Pison et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…They include multi-breath nitrogen wash-out to evaluate small airway function, different imaging modalities and analytic strategies (e.g. high-resolution computed tomography), novel assessments of immune cell counts, chemokines, cytokines, and circulating cell free DNA ( Belloli et al, 2021 ; Shtraichman and Diamond, 2020 ; Tissot et al, 2019 ; Veraar et al, 2021 ). Some groups are also investigating computational models to estimate a recipient’s risk of CLAD using clinical and multi-omic databases ( Koutsokera et al, 2017 ; Pison et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in an associated ex vivo study, they identified that activated T cells promote specific MMP‐9 production by bronchial epithelial cells trough the CCL2/CCR2 axis in synergy with TGF‐β and initiate epithelial-to-mesenchymal transition ( 40 ). Recently, increased expression of lipocalin-2, which stabilizes MMP-9 activity, was also proposed as potential biomarker to distinguish RAS from BOS patients and stable-LTx patients ( 41 ). TGF-β forms the most potent inducer of CTGF, and CTGF overproduction plays a crucial role in fibrosis development ( 42 , 43 ), but appears to induce fibrosis mostly in the co-presence of TGF-β ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of alpha 2-macroglobulin, ceruloplasmin and antithrombin-3 could discriminate between CLAD and control patients [44]. Lipocalin is another marker involved in macrophage-related innate immunity and was increased in RAS compared with BOS and control [45]. Krebs von den Lungen 6 (KL-6) is produced by damaged pneumocytes, and higher serum concentrations could differentiate RAS from BOS patients, while BAL KL-6 concentrations showed no difference.…”
Section: Blood Biomarkersmentioning
confidence: 99%